Cidade sonora: o popular, o massivo e a cultura letrada nas ondas da Rádio Educadora de Uberlândia (1952-1969) - Martins, Suhellen Souza (2017)
This work aims to analyze the trajectory of Radio Educadora de Uberlândia from its inception in 1952 until the late 1960s when television settles in the city. It seeks to understand how the radio station was inserted and broadened its space in the cultural, social and political environment of the city, what readings it made of Uberlândia and its inhabitants and what model of radiophony was proposed by its leaders. Using documental articles from newspaper and magazines, oral testimonials and program scripts, it seeks to analyze the spaces of leisure and sociability existing in the period, as well as reconstituting the tensions surrounding the creation of the station. It also seeks to analyze the radio experiences of professionals and listeners, dialoguing with their impressions and visions about the city and the broadcasting, contributing to reflection on the backstage of the station, as well as bringing to the fore characters who collaborated for the development of “radiofonia uberlandense” in its golden times. It also reflects on the elements that made up the station's programming, which invested in auditorium programs, freshman and humorous shows, approaching the popular layers, while attending to the wishes of the intellectual elite, using the radio chronicles as space To propagate the image of a modern city and of a solidary, hard-working and civilized people, dictating behavior patterns to the population and contributing to moralizing campaigns of customs.